Resolving Land Disputes Related to Administrative Boundaries between Hanoi City and Hoa Binh Province - Que, Phan Thị Nguyet; Hoa, Dinh Thi Bao; Soat, Hoang Van (VNU Journal of Science: Earth and Environmental Sciences; Vol 34 No 2, 2018)
Implementing Directive 364-CT on resolving land disputes related to administrative boundaries of provinces, districts and communes has been resolved. Based on that the records and maps of administrative boundaries were established with the full nature, legal, accurate and uniform stipulated. However, due to many reasons, the administrative boundary lines are still not clearly identified in the field. Land disputes between Hanoi city and Hoabinh province exist in 7 regions, each region has different characteristics of topography, population, history, culture, economic and social, therefore different solution will be applied for each region. This paper presents approaches for resolving the issue which involves administrative boundaries between Hanoi city and Hoabinh province. The research results later can be considered as a professor experience in land disputes resolving in the other provinces in the country... Keywords: Administrative boundaries, land disputes relation, opinion.